Implications of the application of ERP integrated management software on management control function in the organization (company SEDAIR El-Hadjar) - benkara, imene (Journal of Research in Finance and Accounting, 2022)
This study aims to present the implications of the application of ERP integrated management software on management control function. The latter is one of the necessary means for the leadership of the institution through the control and management of activities and coordination among them. Where this requires the application of the information system in an electronic form that allows the upgrading of operations in a homogeneous and rapid manner between the internal and external departments and units. In order to know the practical reality of the application of integrated software in Algerian institutions, specifically at the level of the management control function, we decided to present the experience of the company SEDAIR El-Hadjar with its application of a software called “SAP- Application and Production System -”. One of the most important operations that this system provided to the management supervisor, which facilitated his tasks, is to know the change in the stock of goods in a short time.